Laser Surgery of Soft Tissue in Orthodontics: Review of the Clinical Trials - Seifi, Massoud; Matini, Negin Sadat (Journal of Lasers in Medical Sciences, 2017)
Introduction: Recently, a wide variety of procedures have been done by laser application in Orthodontics. Apart from the mentioned range of various treatments, laser has become a tool for many soft tissue surgeries as an alternative to conventional scalpel-based technique during orthodontic treatments in the management of soft tissue. Due to scarce information in the latter subject, this study was designed in order to include clinical trials that included soft tissue ablation by laser in orthodontics. Methods: Literature was searched based on PubMed and Google Scholar databases in 5 years (2010-2015) with English Language restriction and clinical trial design. Studies that performed soft tissue application of laser during orthodontic treatment were extracted by the authors. Results: Only eight studies met the inclusion criteria. No significant difference were found between laser ablation and conventional scalpel technique in the matter of treatment outcome. However, few issues remained to clarify the differences in the mentioned procedures. Conclusion: Laser performance can be recommended in case of preceding less bleeding and discomfort during surgical procedure. There are still quandaries among clinical application of scalpel-based surgery in aesthetic region with bracket-bonded teeth. Precaution and knowledge regarding the characteristics of laser beam such as wavelength, frequency, power and timing is extremely needed.